A systematic review of research on autism spectrum disorders in Sub-Saharan Africa - Abubakar, A; Ssewanyana, D; Newton, C (Hindawi Publishing, 2016)
The burden of autism spectrum disorders (ASDs) in sub-Saharan Africa (SSA) is not well known. We carried out a systematic review of the literature to identify published work from SSA. We have systematically searched four databases, namely, Medline, PsycINFO, CINAHL, and Child Development & Adolescent Studies, through EBSCO and identified studies from across SSA. Based on predefined inclusion criteria, 47 studies were included in this review. Most of the identified studies (74%) were conducted in only 2 African countries, that is, South Africa and Nigeria. Additionally, most of these studies (83%) were carried out in the last decade. These studies had four major themes: development of measurement tools of ASD in Africa, examining the prevalence of ASD, identifying risk factors and risk markers, and examining psychosocial issues. We identified only a single population level study aimed at documenting the prevalence of ASD and could not identify a single case-control study aimed at examining a comprehensive set of potential risk factors. All intervention studies were based on very small sample sizes. Put together, our findings suggest that current evidence base is too scanty to provide the required information to plan adequately for effective intervention strategies for children with ASD in Africa.